2015
DOI: 10.1007/s11219-015-9289-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk orientation in software testing processes of small and medium enterprises: an exploratory and comparative study

Abstract: Risk orientation in testing is an important means to balance quality, time-tomarket, and cost of software. Especially for small and medium enterprises (SME) under high competitive and economic pressure, risk orientation can help to focus testing activities on critical areas of a software product. Although several risk-based approaches to testing are available, the topic has so far not been investigated in the context of SME, where risks are often associated with business critical issues. This article fills the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 31 publications
0
20
0
3
Order By: Relevance
“…However, the guidance of risk-based testing by software quality models is of high practical importance. In previous studies (Felderer and Ramler 2014a, b;Felderer and Ramler 2016), we found that making testing more effective in terms of (1) detecting additional defects in testing such that fewer defects slip through to the field as well as (2) prioritization for detecting most critical defects first to reduce the overall stabilization costs and time are essential benefits of risk-based testing. Both aspects of effectiveness can be addressed by suitable software quality factors (systematically) selected from quality models.…”
Section: Risk-based Testingmentioning
confidence: 81%
“…However, the guidance of risk-based testing by software quality models is of high practical importance. In previous studies (Felderer and Ramler 2014a, b;Felderer and Ramler 2016), we found that making testing more effective in terms of (1) detecting additional defects in testing such that fewer defects slip through to the field as well as (2) prioritization for detecting most critical defects first to reduce the overall stabilization costs and time are essential benefits of risk-based testing. Both aspects of effectiveness can be addressed by suitable software quality factors (systematically) selected from quality models.…”
Section: Risk-based Testingmentioning
confidence: 81%
“…Although the process of debugging software during its design phase costs 4-5 times less than fixing bugs after its release (Jones and Bonsignour 2011), it is a non-trivial task that consumes a significant part of budgets and companies' effort. It could be less impactful for a big companies and software houses; however, SMEs operating often with limited budgets and resources (Felderer and Ramler 2016) are becoming more and more focused on techniques allowing automation and adequacy of the testing process, to be competitive in relation with big players in the market in terms of software quality, optimization of the development cost, and timeto-market factor.…”
Section: Context and Related Workmentioning
confidence: 99%
“…More objective oriented process are followed for risk management only for the large enterprises not for the small ones. Informed decisions can be taken if risk information is not vague in nature 10 . Risk based testing can be integrated in the industrial process 11 .…”
Section: Fig 8: Misuse Cases Example Templatementioning
confidence: 99%